Searches for possible T-odd and P-odd short range interactions using polarized nuclei - Chu P. H. (EPJ Web of Conferences, 2014)
Various theories predict the possible existence of T-odd and P-odd shortrange forces between spin ½ fermions, proportional to S・r where S is the fermion spin and r is the separation between particles. We use ensembles of polarized nuclei and an un-polarized mass to search for such a force over sub-mm ranges. We established an improved upper bound on the product gsgpn of the scalar coupling to particles in the un-polarized mass and the pseudo-scalar coupling of polarized neutrons for force ranges from 10−4 to 10−2 m, corresponding to a mass range of 2・10−3 to 2・10−5 eV for the exchange boson [1].